2015
DOI: 10.1111/jphp.12339
|View full text |Cite
|
Sign up to set email alerts
|

Tablets compressed with gastric floating pellets coated with acrylic resin for gastro retention and sustained release of famotidine: in-vitro and in-vivo study

Abstract: The experimental results indicated that the optimized formulation did offer a new gastro retention and sustained release approach to enhance the oral absorption of famotidine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Our experimental results also showed that PH 301 could prevent the pellets from being damaged. This is consistent with the experimental results by Xiaole Qi et al [ 26 ]. The best formulation of pulseⅠwas finally determined to be amoxicillin 69%, Avicel PH 301 25%, HPMC E5 4% and PVPP 2%.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Our experimental results also showed that PH 301 could prevent the pellets from being damaged. This is consistent with the experimental results by Xiaole Qi et al [ 26 ]. The best formulation of pulseⅠwas finally determined to be amoxicillin 69%, Avicel PH 301 25%, HPMC E5 4% and PVPP 2%.…”
Section: Resultssupporting
confidence: 94%
“…Based on the single factor experiment, four factors and three levels Box–Behnken design was carried through to get an optimal composition of the tablets by investigating the effect of the coating weight of Eudragit L30 D-55, the coating weight of AQOAT AS-HF, the extrusion screen aperture and the compression forces. The dependent variables and independent variables were related by mathematical relationships [ 26 ]. The polynomial equations obtained were:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastro-retentive systems (floating tablets, pellets or beads) were successfully developed and evaluated for several category of drugs like antihistamines (cetrizeine, famotidine, ranitidine), NSAIDS (ketorolac, celecoxib), antibiotics (metronidazole, ofloxacin, amoxicillin), antidiabetics (metformin, repaglinide) and many more [8][9][10][11][12][13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Obtention of immediate-release systems, with a focus on masking drug flavor (Hamedelniel, Bajdik, Pintye-Hódi, 2010;Issa et al, 2012b;Patel, Patel, Patel, 2010);  Controlled-release (Abbaspour, Sadeghi, Garekani, 2008;Bialleck, Rein, 2011;Cantor, Hoag, Augsburger, 2009a;Cantor, Hoag, Augsburger, 2009b;Franc et al, 2015;Ghanam, Kleinebudde, 2011;Ghosh, Chakraborty, 2013;Han et al, 2013;Heckötter et al, 2011;Hung et al, 2015;Ríos, Ghaly, 2015;Roblegg et al, 2011;Szkutnik-Fiedler et al, 2014;Wang et al, 2015;Xu, Liew, Heng, 2015;You et al, 2014);  Improvement in dissolution of poorly soluble drugs (Abdalla, Mader, 2007;Abdalla, Klein, Mader, 2008;Chopra, Venkatesan, Betageri, 2013;Ibrahim, El-Badry, 2014;Lu et al, 2009;Patel et al, 2016);  Gastro-retentive systems/ floating systems (Amrutkar, Chaudhari, Patil, 2012;Li et al, 2014;Pagariya, Patil, 2013;Qi et al, 2015;Zhang et al, 2012);  Enteric release/gastro-resistant systems (Andreo-Filho et al, 2009;Ghanam, Kleinebudde, 2011;Pund et al, 2010);  Improvement of plant extract or active ingredient stability (Araújo-Junior et al, 2013;Beringhs et al, 2012;Bu...…”
Section: Multiparticulate Dosage Forms and Drug Delivery Systemsmentioning
confidence: 99%